Investigation of aromatase inhibitory activity of metal complexes of 8-hydroxyquinoline and uracil derivatives - Prachayasittikul V; Pingaew R; Nantasenamat C; Prachayasittikul S; Ruchirawat S; Prachayasittikul V (Dove Medical Press, 2014)
Veda Prachayasittikul,1 Ratchanok Pingaew,2 Chanin Nantasenamat,3 Supaluk Prachayasittikul,3 Somsak Ruchirawat,4,5 Virapong Prachayasittikul1 1Department of Clinical Microbiology and Applied Technology, Faculty of Medical Technology, Mahidol University, Bangkok, Thailand; 2Department of Chemistry, Faculty of Science, Srinakharinwirot University, Bangkok, Thailand; 3Center of Data Mining and Biomedical Informatics, Faculty of Medical Technology, Mahidol University, Bangkok, Thailand; 4Laboratory of Medicinal Chemistry, Chulabhorn Research Institute, 5Chulabhorn Graduate Institute, Bangkok, Thailand Purpose: Estrogens play important roles in the pathogenesis and progression of breast cancer as well as estrogen-related diseases. Aromatase is a key enzyme in the rate-limiting step of estrogen production, in which its inhibition is one strategy for controlling estrogen levels to improve prognosis of estrogen-related cancers and diseases. Herein, a series of metal (Mn, Cu, and Ni) complexes of 8-hydroxyquinoline (8HQ) and uracil derivatives (4–9) were investigated for their aromatase inhibitory and cytotoxic activities. Methods: The aromatase inhibition assay was performed according to a Gentest™ kit using CYP19 enzyme, wherein ketoconazole and letrozole were used as reference drugs. The cytotoxicity was tested on normal embryonic lung cells (MRC-5) using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Results: Only Cu complexes (6 and 9) exhibited aromatase inhibitory effect with IC50 0.30 and 1.7 µM, respectively. Cytotoxicity test against MRC-5 cells showed that Mn and Cu complexes (5 and 6), as well as free ligand 8HQ, exhibited activity with IC50 range 0.74–6.27 µM. Conclusion: Cu complexes (6 and 9) were found to act as a novel class of aromatase inhibitor. Our findings suggest that these 8HQ–Cu–uracil complexes are promising agents that could be potentially developed as a selective anticancer agent for breast cancer and other estrogen-related diseases. Keywords: aromatase inhibitor, anticancer, metal-based compound